Karakteristik Desain Poster Film Animasi Amerika Serikat - Christianna, Aniendya; Pranata, Moeljadi (Institute of Research and Community Outreach - Petra Christian University, 2010)
An animated film will end in vain no matter how well it is without the support of media to give buzz to the message of the film. One of the most important advertising media in promoting an animated film is the poster. Because the animation movie poster is the leading medium which deals directly with the target audience in delivering information about the film before the screening of the film takes place. So visualization of the poster that includes the composition of verbal and non verbal language deserves more attention in its design.